Clinical Features of Miller-Fisher Syndrome in Pregnancy - Masanori Ono; Hideki Sato; Mayu Shirahashi; Noriko Tomioka; Julia Maeda; Keiko Watanabe; Tomoko Amagata; Toshiyuki Ikeda; Kazumi Yakubo; Tatsuro Fukuiya (Case Reports in Obstetrics and Gynecology)
Miller-Fisher syndrome (MFS) is recognized as a variant of Guillain-Barré syndrome (GBS). MFS is a rare disorder that is characterized by the acute onset of ophthalmoplegia, ataxia, and areflexia/hyporeflexia. MFS has a higher incidence in Asia, where the incidence is estimated to be 18%–26% of GBS compared with 3%–5% in the West. The differential diagnosis of MFS includes Wernicke’s encephalopathy (WE) which is characterized by a clinical triad (nystagmus and ophthalmoplegia, mental status changes, and ataxia), myasthenia gravis, and brainstem stroke. The association between MFS and pregnancy has not been reported previously. Here, we describe the clinical features of a pregnant woman in early pregnancy with MFS. This case highlights the fact that it is necessary to establish an accurate diagnosis based on the details from the patient’s history on appropriate complementary testing in a pregnant patient with MFS.